2021
DOI: 10.3389/fvets.2021.647108
|View full text |Cite
|
Sign up to set email alerts
|

Frequency, Stressfulness and Type of Ethically Challenging Situations Encountered by Veterinary Team Members During the COVID-19 Pandemic

Abstract: Ethically challenging situations (ECS) are common in veterinary settings and can lead to moral stress. However, there is no published information about how a global pandemic affects the frequency and types of ECS encountered by veterinary team members. An online mixed methods survey was developed to determine the frequency, stressfulness and types of ECS experienced by veterinarians, animal health technicians and veterinary nurses since the advent of the global COVID-19 pandemic in March 2020. Responses from 5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
58
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 35 publications
(60 citation statements)
references
References 69 publications
2
58
0
Order By: Relevance
“…Decision making regarding the provision of appropriate care for animals has been, and continues to be, a potential source of stress for veterinarians [17]. During and after the pandemic, veterinarians had additional considerations to take into account when assessing cases, and a recent survey of 540 veterinarians revealed that 46% found decision making around service provision and visits "ethically challenging" during the COVID-19 pandemic [18]. It is possible that pre-existing stressors for veterinarians may have been exacerbated by the accumulation of challenges that presented in day-to-day practice as well as those associated with the pandemic, including teleconsultation.…”
Section: Discussionmentioning
confidence: 99%
“…Decision making regarding the provision of appropriate care for animals has been, and continues to be, a potential source of stress for veterinarians [17]. During and after the pandemic, veterinarians had additional considerations to take into account when assessing cases, and a recent survey of 540 veterinarians revealed that 46% found decision making around service provision and visits "ethically challenging" during the COVID-19 pandemic [18]. It is possible that pre-existing stressors for veterinarians may have been exacerbated by the accumulation of challenges that presented in day-to-day practice as well as those associated with the pandemic, including teleconsultation.…”
Section: Discussionmentioning
confidence: 99%
“…[16]. Conflicts between the interests of the owner and the interests of the animal are one of the most common ethical challenges faced by veterinarians and veterinary team members [37,38,[59][60][61][62]]. Yet, it is possible for veterinarians, like other healthcare professionals, to be influenced by considerations other than the needs of the client and the patient.…”
Section: Conflicts Of Interestmentioning
confidence: 99%
“…During the COVID-19 pandemic, declared by the World Health Organization on 11 March 2020 ( 7 ), veterinarians, animal health technicians, veterinary nurses, and other health professionals (“veterinary team members”) encountered ECS not documented in previous surveys. A global survey of 540 veterinary team members, found that such ECS included conflict between personal well-being and professional role, and deciding what constitutes an essential veterinary service ( 8 ). They also encountered well-documented ECS, such as dealing with clients with financial limitations, and conflicts between the interests of the animal and those of the client.…”
Section: Introductionmentioning
confidence: 99%
“…They also encountered well-documented ECS, such as dealing with clients with financial limitations, and conflicts between the interests of the animal and those of the client. Of those experiencing an increase in ECS since the beginning of the COVID-19 pandemic, the median frequency of ECS encountered by respondents increased from several times per month to several times per week (Spearman rank correlation 0.619, p < 0.0001) ( 8 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation